A relação família-escola nos periódicos científicos brasileiros (2000-2013) - Oliveira, Luana Maria de (2015)
This work aims to analyze the family-school relationship by means of scientific articles, in order to understand how it has been characterized in Brazilian journals from 2000 to 2013 and seeking to contribute to the studies concerning this topic. For this we considered relevant to conduct this analysis starting with the political, economic and cultural context of our present society, that is, trying to understand the relations between State, Family and School within the capitalist system and in face of globalization. We conducted a bibliographic search that involved an ordered set of procedures, given the object of research and its main objective, and which consisted of three steps: surveying library materials and selecting the 46 articles analyzed in this research; analyzing the selected studies, inspired by "content analysis" as an analytical technique, in order to identify information, data and relations between the selected articles; and performing an integrating synthesis of solutions, in which we presented the final product of the investigation process, which resulted from the analysis and reflection on the documents. The analysis revealed six categories, representing the major highlights of the articles selected for this research. The first is the category of types of family-school relationship, in which two predominant types were appointed. One is an unidirectional relationship, and the other is marked by partnership.The articles showed that the school institution is the main responsible for family-school approximation, represented mainly by the teachers. As for the difficulties faced in family-school relationship, the analysis showed, among other factors, that the asymmetry in the family-school relationship reflects the school difficulty in understanding what is the true reality experienced by their students, as well as their families, and vice versa. As ways of relationship between the family and the school, the analysis showed that these have been done through agenda books, notes, parents meetings and meetings at the beginning and end of classes, homework, participation in scheduled events due to commemorative dates, financial contributions, support and maintenance for the proper development of the school. As for the social role of family and school, the articles highlighted that both institutions have different social functions in relation to the good school performance of the student, and share the task of educating children and young people for their successful development and participation in society. The last category resulting from the analysis discussed the school and family practicespointed by the articles.